2016
DOI: 10.1177/1362361316630201
|View full text |Cite
|
Sign up to set email alerts
|

Open-trial pilot study of a comprehensive outpatient psychosocial treatment for children with high-functioning autism spectrum disorder

Abstract: This study examined the feasibility and initial outcomes of a comprehensive outpatient psychosocial treatment (MAXout) for children aged 7-12 years with high-functioning autism spectrum disorder. The 18-week treatment, two 90-minute sessions per week, included instruction and therapeutic activities targeting social/social communication skills, facial emotion recognition, non-literal language skills, and interest expansion. A behavioral system was implemented to reduce autism spectrum disorder symptoms and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
1
0
7
Order By: Relevance
“…Mind Reading: The Interactive Guide to Emotions ) (Lacava et al, 2007, 2010; Lopata et al, 2012, 2013, 2016; Thomeer et al, 2015), with Lopata and colleagues (2019) evaluating Mind Reading as one part of a comprehensive school-based intervention program. The only study that utilized CAM-C outside of the Mind Reading intervention was an open pilot study of a comprehensive outpatient psychological treatment for children with ASD (Lopata et al, 2017), in which they found significant improvement on CAM-C scores following intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Mind Reading: The Interactive Guide to Emotions ) (Lacava et al, 2007, 2010; Lopata et al, 2012, 2013, 2016; Thomeer et al, 2015), with Lopata and colleagues (2019) evaluating Mind Reading as one part of a comprehensive school-based intervention program. The only study that utilized CAM-C outside of the Mind Reading intervention was an open pilot study of a comprehensive outpatient psychological treatment for children with ASD (Lopata et al, 2017), in which they found significant improvement on CAM-C scores following intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Finalmente, la mayor parte de los estudios han tenido lugar en el continente americano (47,3%), predominando EE.UU. (Doernberg et al, 2021;Kabashi y Epstein, 2017;Lopata, et al, 2017;Morgan, et al, 2018;Radley et al, 2018;Radley et al, 2017;Sabey et al, 2020), aunque también se encuentra algún trabajo en Canadá (D'Amico y Lalonde, 2017) y en Brasil (Cassia et al, 2020).…”
Section: Discussionunclassified
“…Otros se centran en desarrollar directamente las normas del juego para favorecer la inclusión y evitar conflictos o rechazos (Doernberg et al, 2021;Gal et al, 2016;Sabey et al, 2020). Las habilidades interpersonales son trabajadas en estudios como el de Bonete et al (2016), Gal et al (2016), D'Amico y Lalonde (2017), Lopata et al (2017), Morgan et al (2018), Radley et al (2018), y Kylliänen, et al (2020.…”
Section: Variables Metodológicasunclassified
See 2 more Smart Citations